EARE-1, a Transcriptionally Active Ty1/Copia-Like Retrotransposon Has Colonized the Genome of Excoecaria agallocha through Horizontal Transfer - Huang, Jianhua; Wang, Yushuai; Liu, Wenwen; Shen, Xu; Fan, Qiang; Jian, Shuguang; Tang, Tian (Frontiers in Plant Science, 2017)
Long terminal repeat (LTR) retrotransposons constitute the majority of the content of angiosperm genomes, but their evolutionary dynamics remain poorly understood. Here, we report the isolation and characterization of a putative full-length (~9550 bp) Ty1/copia-like retrotransposon in Excoecaria agallocha and its evolution in Euphorbiaceae. The so-called EARE-1 is phylogenetically closely related to RIRE-1 from O. australiensis, and has proliferated recently (~7.19 Mya) in the E. agallocha genome. An RT-PCR analysis revealed substantial transcription of EARE-1 in all examined organs (leaves, staminate flowers, pistillate flowers, seeds, and roots) in unstressed E. agallocha plants and indications of elevated expression under stress. We conducted sequence analyses of 256 RT-RH fragments (~860 bp) of EARE-1 from 34 species representing four subfamilies of Euphorbiaceae that exist in China. EARE-1 copies from two Excoecaria species and Phyllanthus urinaria showed incongruent phylogeny with the host species and exhibited high sequence similarity to the host genes, suggesting a horizontal transfer from P. urinaria to the common ancestor of Excoecaria. However, SSAP analysis detected no new insertions of EARE-1 among full-sibling progeny plants of E. agallocha, despite considerable SSAP polymorphisms among half-siblings. EARE-1 is the first transcriptionally active Ty1/copia-like retrotransposon isolated from E. agallocha. Our results provide empirical evidence of the horizontal transfer of LTR retrotransposons in plants, and may suggest a significant role of post-transcriptional host control in the life cycles of transposable elements.